Eksistensi Masyarakat Adat Jawa Blitar Dalam Proses Larung Sesaji Dalam Perspektif Hukum Adat Dan Islam - Haidar Danendra Febrian Ar Rafi; Khanza Aoera Dievana; Dimas Herdian Nugrahimsyah; Sandrina Rahma Nurvita; Fadhilah Dzakwan Syarif (Lembaga Pengembangan Kinerja Dosen, 2024)
Local wisdom is considered as part of the culture and identity of indigenous peoples, which contains values, norms, ethics, beliefs, customs and traditions developed through social and cultural interactions. This research focuses on one of the traditions in Indonesia, namely the larung offering ceremony. Larung offerings is a religious ritual as a form of gratitude to God. In this research, it was found that the Javanese Blitar indigenous people still maintain the tradition of larung offerings as part of their culture and beliefs. The research method used is a literature study by collecting data from written sources. The purpose of writing this article is to find out the existence of the Blitar Javanese traditional community carrying out offerings and how customary and Islamic law influences this process.